Exploring Tiktok Application in Learning Speaking for EFL Student in High School - Muhammad Haykal Habibillah; Martriwati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study uses a mixed-methods approach to investigate how TikTok affects EFL learners' improvement of speaking abilities. Ten chosen students participated in semi-structured interviews and completed a questionnaire (N = 202) to gather data. TikTok usage and speaking performance were found to be significantly positively correlated in the quantitative study; regression results showed that 34.5% of the students' speaking success was attributable to TikTok. Qualitative results supported this, demonstrating that students saw TikTok as a fun and laid-back platform that boosted their vocabulary, confidence, and pronunciation. Despite certain difficulties, such as distractions, students used self-regulated learning techniques to stay focused. The findings indicate that TikTok can be a useful additional tool for improving EFL speaking abilities.